The Philippine environment - Padilla, Amerina; Paz, Milo Alto. (Manila Ibon Foundation and AsiaVisions Media Foundation, 1998)
A documentary on the state of Philippine environment.
A production of IBON Foundation Inc. and AsiaVisions Media Foundation through the assistance of MISEREOR.
VHS.
Keywords: Environmental science